Clinically significant intra-day variability of serum progesterone levels during the final day of oocyte maturation: a prospective study with repeated measurements. Issue 8 (23rd July 2019) - González-Foruria, I; Rodríguez, I; Martínez, F; Rodríguez-Purata, J; Montoya, P; Rodríguez, D; Nicolau, J; Coroleu, B; Barri, P N; Polyzos, N P
Abstract: STUDY QUESTION: Is there significant variability in progesterone levels during the final day of oocyte maturation in women undergoing ovarian stimulation? SUMMARY ANSWER: Progesterone levels drop from the basal level up to 44% during the final day of oocyte maturation in women undergoing ovarian stimulation. WHAT IS KNOWN ALREADY: It has been suggested that elevated progesterone levels on the final day of ovarian stimulation may be related to poorer outcomes in in vitro fertilization fresh cycles due to a negative impact on the endometrium. However, despite conflicting results regarding the actual effect of progesterone on pregnancy rates and the lack of a well-established cut off, currently many IVF patients have their embryo transfer deferred when progesterone values surpass a threshold of 1.5 ng/ml on the day of ovulation triggering. STUDY DESIGN, SIZE, DURATION: This was a prospective cohort study conducted in 22 oocyte donors of a university-affiliated fertility centre between November 2017 and January 2018. We calculated the sample size to detect a difference of 15% between the first and last progesterone measurements with a 5% false-positive rate in a two-sided test with 80% statistical power and a 95% confidence interval (CI). PARTICIPANTS/MATERIALS, SETTING, METHODS: Progesterone circulating levels were evaluated at four different times during the final day of oocyte maturation (08:00, 12:00, 16:00 and 20:00) before ovulation triggering in healthy oocyte donors. A flexible antagonist protocol was used, and ovarian stimulation was achieved with recombinant follicle-stimulating hormone (FSH) in all cases. The pairwise percentage differences in progesterone levels for each patient were calculated. Univariate linear regression analysis was adopted in order to evaluate variables associated with progesterone levels on the first measurement. The intra-day variability of progesterone was analysed using mixed models. MAIN RESULTS AND THE ROLE OF CHANCE: Mean serum progesterone values at 08:00, 12:00, 16:00 and 20:00 were 1.75 ng/ml, 1.40 ng/ml, 1.06 ng/ml and 0.97 ng/ml. The progesterone difference between 08:00 and 20:00 was 0.77 (95% CI, 0.56–0.99), which is equivalent to a 44% decline in the mean progesterone values between the first (08:00) and the last determination (20:00; P  < 0.001). Among those patients with basal (08:00) progesterone levels >1.5 ng/ml ( n  = 10), 70% ( n  = 7) showed levels reduced to <1.5 ng/ml on the last determination of the day (20:00). A mixed model analysis revealed that the progesterone reduction during the day was significantly associated with time and total recombinant FSH dose administered. LIMITATIONS, REASONS FOR CAUTION: Only young healthy oocyte donors stimulated with an antagonist protocol using recombinant FSH were included. Extrapolation to the general IVF population, with different stimulation protocols and gonadotropins, needs to be confirmed. WIDER IMPLICATIONS OF THE FINDINGS: This study suggests that a single progesterone determination on the final day of oocyte maturation is not reliable enough to make clinical decisions due to the enormous variation in progesterone during the day. Further studies are needed to better define the impact of the follicular progesterone rise on the endometrium of IVF cycles. STUDY FUNDING/COMPETING INTEREST(S): Funding was granted from Fundació Santiago Dexeus Font. N.P.P. received unrestricted grants and/or lectures fees from Roche Diagnostics, MSD, Merck, Ferring Pharmaceuticals, IBSA, Theramex and BESINS International, not associated with the current study. The remaining authors have no competing interests. TRIAL REGISTRATION NUMBER: Clinicaltrials.gov NCT03366025.